Evidence of Cascading Subglacial Water Flow at Jutulstraumen Glacier (Antarctica) Derived From Sentinel‐1 and ICESat‐2 Measurements. Issue 20 (19th October 2021) - Neckel, Niklas; Franke, Steven; Helm, Veit; Drews, Reinhard; Jansen, Daniela
Abstract: Migration of subglacial water underneath thick Antarctic ice is difficult to observe directly but is known to influence ice flow dynamics. Here, we analyze a 6‐year time series of displacement maps from differential Sentinel‐1 SAR interferometry (DInSAR) in the upstream region of Jutulstraumen Glacier. Our results reveal short‐term (between 12 days and 1 year) interconnected subsidence‐ and uplift events of the ice surface, which we interpret as a pressure response to the drainage and filling of subglacial lakes. This indicates an episodic cascade‐like water transport with longer quiescent phases in a dynamically stable glacial setting. Abrupt events appear in the DInSAR time series and are confirmed by ICESat‐2 altimetry. The events can be traced for a 1‐year period along a ∼ 175 km flow path. We are able to observe the migration of subglacial water with unprecedented spatial and temporal resolution, providing a new observational baseline to further develop subglacial hydrological models. Plain Language Summary: Subglacial lakes and the movement of subglacial water play an important role in the way how ice flows in the Antarctic Ice Sheet. The drainage and filling of subglacial lakes is reflected in subsidence and uplift at the ice surface, which can be monitored by satellite based elevation measurements. In this study, we detect these elevation changes of the ice surface at the onset of Dronning Maud Land's largest glacier (Jutulstraumen Glacier, Antarctica). We register a number of connected events which show us where and when subglacial water moves downstream. We find that the water flows similarly to a self‐tipping swimming pool bucket: water beneath the ice is localized and abruptly moves from one place to another after some time has passed. Using airborne radar‐sounding techniques, we find that the water flows along preferential flowpaths in the subglacial system. These are the first confirmed subglacial water movements in central Dronning Maud Land, an area where no subglacial water flow has been observed previously. The episodic nature of water flow is a new observation that will help us to understand how the subglacial water forms its own pluming system beneath these large glaciers. Key Points: Sentinel‐1 DInSAR estimates reveal a ∼175 km flow path of a cascade‐like chain of subglacial water propagation over a 1‐year period High‐resolution ultra‐wideband radar data show no characteristic lake bed reflections and suggests water transport via a local trough system We find evidence of highly dynamic water transport in a static glacial stetting providing a benchmark dataset to improve modeling results